Preparation and characterization of calcium silicate for CO2 sorption - Kale, Kishor B.; Raskar, Reshma Y.; Rane, Vilash H.; Gaikwad, Abaji G. (Adsorption Science & Technology, 2012)
An attempt has been made to develop different samples of calcium silicate and to screen these samples for CO2 sorption and alkalinity in order to achieve maximum CO2 sorption. The CO2 sorption capacity of these samples was examined at different temperatures. Various methods such as solid-solid fusion, sol-gel, molten salt and templates (CTAB, cetyltrimethylammonium bromide or Aliquat 336, tricaprylmethylammonium chloride) were used to prepare the calcium silicate samples. The solid mass of calcium silicate samples were obtained by calcining the solid product obtained in an atmosphere of air or helium at 900 degrees C for 3 hours. The calcium silicate samples were characterized for surface area, alkalinity, scanning electron microscopic images and X-ray diffraction patterns. The temperature profile of CO2 sorption by calcium silicate was studied in the temperature range of 40-850 degrees C. Our results showed that the alkalinity and surface area of calcium silicate were in the range from 2.35 to 20 mmol g(-1) and 1.4 to 10 m(2) g(-1), respectively. The sorption of CO2 at 500 degrees C over calcium silicate for the different Ca/Si mol ratio (range: 1-6) was found to be in the range from 3.12 to 29.96 wt%. Addition of a promoter such as sodium, potassium, caesium and lanthanum was found to enhance the sorption of CO2 by calcium silicate. Several samples of different mol ratios of Ca/Si prepared by different methods were tested for the sorption of CO2 at 500 degrees C.

Enhanced mineralization of gaseous organic pollutant by photo-oxidation using Au-Doped TiO2/MCM-41 - Tangale, Nilesh P.; Belhekar, Anuja A.; Kale, Kishor B.; Awate, Shobhana V. (Water Air and Soil Pollution, 2014)
The synthesis, characterization, and photocatalytic evaluation of titania-loaded MCM-41 with and without Au doping are reported in the present study. The samples were characterized by powder XRD, TEM, low temperature N-2 adsorption/desorption, UV-Vis, and FTIR. UV-induced vapor-phase photo-oxidation of acetone was used as a probe reaction to study the role of Au in mineralization of volatile organic compounds (VOCs), viz. acetone at different concentrations. The doping of Au in titania-loaded MCM-41 resulted in the decrease of BET surface area, total pore volume, and average pore size. UV-Vis diffuse reflectance spectra of Au-doped titania-loaded MCM-41 showed the red shift in their absorption bands compared to titania-loaded MCM-41. The activity of mineralization of acetone by photocatalysis for 2 % Au-doped titania-loaded MCM-41 was found to be similar to 1.6 times higher than titania-loaded MCM-41. The presence of cocatalytic nanosized gold might be responsible for their enhanced activity on account of the delayed recombination of electron/hole pair. Although, almost complete mineralization of acetone was observed irrespective of the initial concentration of acetone in air (up to 3.72 mol%) by all the catalysts, 2 wt.% Au-doped titania-loaded MCM-41 has shown the most enhanced activity.
Keywords: Acetone; Doping; Gold; Mineralization of VOCs; Photo-oxidation; TiO2/MCM-41